Nimble and Ready to Mingle: Transposon Outbursts of Early Development. Issue 10 (October 2018) - Rodriguez-Terrones, Diego; Torres-Padilla, Maria-Elena
Abstract : Transposable elements are the largest individual constituent of mammalian genomes. These elements are highly diverse, a consequence of the multiplicity of genomic habitats that they inhabit and of the complex evolutionary histories that they have developed therein. Intriguingly, a surge of transposable element transcription occurs during mammalian preimplantation development, contributing to the establishment of totipotency and pluripotency and to the activation of the embryonic genome. However, it remains an open question how such an evolutionarily divergent set can mediate such conserved developmental processes. Here, we review transposable element diversity across mammals and their evolutionary significance. We also discuss the implications that their high evolutionary divergence has for the regulation of preimplantation development across mammals. Highlights: Transposable elements are extensively transcribed during early development in a stage-specific manner in both mice and humans. Stage-specific transcriptional activity of transposable elements reflects a complex interplay between their co-option by host regulatory programs and their own selective pressure to replicate within the germline. Despite their limited conservation across mammals, transposable elements have been co-opted into regulatory functions during early development. The ERV-L family of endogenous retroviruses can function as alternative promoters during embryonic genome activation in both mice and humans, and despite its lack of sequence conservation, an orthologous transcription factor binds their long terminal repeat (LTR) in both species. The timely transcription of some transposable elements, such as L1 in mice, is necessary for developmental progression.